The Importance of Computers with Matlab Software in the Teaching and Learning of Geometry in Space - Costică, Lupu (International Journal of Mathematical Research, 2014)
The aim of this study is to evaluate the efficiency of using computers with MATLAB software in the teaching-learning of Geometry in middle-school, by the students from the specialization of Mathematics, “Vasile Alecsandri” University of Bacau. During the pedagogical practice stage, the students in the 3rd year, although better trained in Mathematics than the students from other departments, face various problems related to their practical skills in using the computer in teaching, as well as to their lack of teaching experience. The research was conducted at the National Pedagogical College “Ştefan cel Mare” from Bacau and consisted in assisting and observing 28 lessons of Mathematics and 28 lessons of Information and Communication Technologies, involving a group of 200 students from grades 1-4, 180 middle-school students and 40 teachers of various specializations. The applied tests and questionnaires have shown the efficacy of using the computer in building active thought and competences in the graphical representation of geometrical figures and shapes, as well as in solving problems of plane collinearity. In relation to these problems, we are looking for a solution to comprise the best teaching-learning strategies using the calculus technique. With nearly 5000 functions, the MATLAB software menu provides techniques for acquiring knowledge in an electronic format, calculus techniques, explanatory mathematical texts, graphs, sounds and diagrams, e-learning solutions, including online testing and evaluation, as well as web-based learning tools designed for Mathematics (www.maplesoft.com).